2023
DOI: 10.1111/jre.13123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged stimulation with heated tobacco products (Ploom TECH+) on gingival epithelial cells

Abstract: Objective and Background: Heated tobacco products have recently become commercially available. These products, as well as combustible cigarettes, produce aerosols; the risk of various diseases associated with heated tobacco products may be the same or higher than that with combustible cigarettes. In this study, we examined the effect of Ploom TECH + extract on gingival epithelial cells.Methods: Tobacco leaves from Ploom TECH + tobacco capsules and water were mixed and heated; the supernatant subsequently colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Similarly, two studies on HTP confirmed gene modifications when oral cells were exposed to HTP [108,109]. When compared to ECS and CS, HTP seems to modify oral cell function [111].…”
Section: Main Results Of the Included Studiesmentioning
confidence: 76%
See 2 more Smart Citations
“…Similarly, two studies on HTP confirmed gene modifications when oral cells were exposed to HTP [108,109]. When compared to ECS and CS, HTP seems to modify oral cell function [111].…”
Section: Main Results Of the Included Studiesmentioning
confidence: 76%
“…Regarding studies on oral cancer cells [108], conclusive hypotheses could not be drawn, since some papers suggested that ENDS and HTP might be possible alternatives to cigarette smoking. In contrast, other studies concluded that its effects are similar to those of conventional smoking [109][110][111].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation